When Is Moving a Cursor With a Computer Mouse Intuitive?. (April 2020) - Brenner, Eli; de Graaf, Myriam L.; Stam, Marielle J.; Schonwetter, Margreet; Smeets, Jeroen B. J.; van Beers, Robert J.
People have a good intuition of how to move a computer mouse to place a cursor at a desired position on a screen. This is surprising because the hand and the mouse are at different locations and they generally move in different directions and over different distances. But using a computer mouse is not always intuitive: try positioning a cursor after turning the mouse by 90° in your hand. To examine when using a computer mouse is intuitive, we asked participants to move a cursor to targets on a screen by moving a mouse along a surface. We varied the orientation of this surface in space and that of the mouse in the hand. Participants performed best when the mapping between hand and cursor motion was close to what we are accustomed to, either in space or relative to the forearm.